Tre danske jøder fra Sankt Thomas - Labrosse, Anna (Rambam. Tidsskrift for jødisk kultur og forskning, 2021)
This article tells the story of the ancestors of Anne Labrosse. It begins with Moise and Rebecca Pomie who came to Saint Thomas in the late 18th century. They settled in Charlotte Amalie with their four children and began a new life as members of a Danish Jewish society. The Jewish community of Saint Thomas was small but growing in the late 18th and early 19th century. They enjoyed the privileges of religious freedom, and during the 19th century the community became fully integrated in the Danish colonial society of Saint Thomas. One of Moise and Rebecca’s children, Esther Pomie, married Isaac Petit, and when she died Isaac married Esther’s sister Rachel. When Isaac died his sister sent her son Frederique Abraham Gabriel Pizzarro to help care for Rachel and the children. They fell in love, but the Jewish community of Saint Thomas would not recognize their marriage, so the couple struggled for eight years before they were declared lawfully married. Rachel and Frederique Pizzarro had four children. One of them was Jacob Pizzarro who would later change his name to Camille Pissarro, move to Paris, and become a world-renowned painter. His uncle Samuel Eugene had four daughters. Two of them, Clara and Rosalie, came back to Denmark where their grandparents had come from. Clara married a Danish captain in Copenhagen in the late 19th century and lived there when the persecutions of World War II began. She was sent to Theresienstadt in 1943 where she was marked “Prominent A”. She featured in a propaganda film made by the Nazis to show off the Nazi working camps as lively and cheerful places to be. She came home to Denmark in the spring of 1945 when the Danes were liberated and lived to be a hundred years old. Her sister, Rosalie, married a Christian pharmacist, and they lived in Denmark, but she died in 1941 before she had the chance to experience the persecutions of the Jews in Denmark.